ANALISIS PELAKSANAAN FUNGSI PENGAWASAN PIMPINAN DI BALAI DIKLAT LINGKUNGAN HIDUP DAN KEHUTANAN (BDLHK) PEKANBARU - Chintya Afhissa; Parjiyana Parjiyana (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2017)
This study aims to investigate the implementation of the supervisory function led to the Training Center of Environment and Forests (BDLHK) Pekanbaru, where the implementation of the supervisory function was measured by four indicators, namely: explain the purpose of the work, set the size of the work, observed the work, and develop a conducive working environment , the type of research that is located in the office of Training Centre of Environment and Forests (BDLHK) Pekanbaru in Riau is descriptive qualitative, that prioritize the list of questionnaires of staff Training Centre of Environment and Forests (BDLHK) Pekanbaru in Riau as a data collector and data collected with this tool later the main raw material used to analyze the state-led oversight functions in the Training Centre of Environment and Forests (BDLHK) Pekanbaru using the interview system. The existence of the research objectives at locations studied were offices Training Center of Environment and Forests (BDLHK) Pekanbaru Riau. There are key informant in informant / respondent that the leadership is section head of education and training and staff Training Center of Environment and Forests (BDLHK) numbered 20 people. techniques used in collecting the data is the census technique for the respondent staff Training Centre of Environment and Forests (BDLHK) and to the leadership of the section head of education and training of researchers use interviewing techniques. Typeand data collection techniques used consist of primary data was collected by using questionnaires and interviews and secondary data were collected using observation, while the analytical techniques in use uses interviews leadership of the section head of education and training and the frequency table of the results of the questionnaire given to the staff Training Center of Environment and Forests (BDLHK). Based on this analysis technique researchers assess and conclude that the level of implementation of the supervisory function led to the Training Center of Environment and Forests (BDLHK) Pekanbaru in Riau can be concluded that the overall supervisory function which is led by the head of the section of education and training obtained information "Good"